Professional-Psychological Orientation of the Future Primary School Teachers in Their Preparation to Work with Socially Neglected Pupils - Valentyn Vovk (Pedagogical Discourse, 2013)
Specific character of professional-psychological preparation of the future primary school teachers to the work with the socially neglected pupils is revealed in the article. It is accented on the essence of professional-psychological orientation, in particular on psychological-pedagogical qualities of personality of teacher, necessary for work with the socially neglected students. In addition the results of theoretical and practical preparation of the future teachers to work with such category of students in the system of pedagogical education, and also results of selective questionnaire of primary school teachers of Khmelnytskyi region, which allowed finding out the positive and negative sides of decision of the noted problem. are represented.